Atypical presentation of cervical necrotizing fasciitis. Case report - Moraga, Javier; Chang, Mauricio; Rodríguez, María (Journal of Oral Research, 2019)
Cervical necrotizing fasciitis (NF) is a soft tissue infection with a low incidence, characterized by rapid progression and high morbidity and mortality. The purpose of this report is to communicate the case of a patient diagnosed with cervical NF and its successful management. A 54-year-old male consulted after suffering from the condition for seven days. It was characterized by bilateral submandibular swelling, accompanied by fever, dysphagia, odynophagia, which were severely affecting the patient’s general health. Physical examination revealed a painful, erythematous cervical swelling. A cervical computed tomography scan was performed, revealing a gaseous collection in the left mucosal pharyngeal space, extending to the glottis, associated with significant deep plane soft tissue emphysema onon the left side of the neck and with possible involvement of the danger space; pertinent lab findings include 19,190/uL leukocytes and 219mg/LCRP. Broad-spectrum antibiotic therapy was initiated with ceftriaxone and clindamycin. Exploratory surgery, lavage and drainage of the collected material were performed. Streptococcus anginosus was isolated by culture. The patient recovered appropriately showing improvement in clinical as well as in inflammatory parameters, being discharged on the ninth day. He is currently receiving periodical checkups in the surgery polyclinic.